2019
DOI: 10.1093/omcr/omz097
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb motor improvement in chronic stroke after combining botulinum toxin A injection and multi-joints robot-assisted therapy: a case report

Abstract: Spasticity is one of the major complications after stroke. Botulinum toxin type A (BoNT-A) injection is commonly used to manage focal spasticity. However, it is uncertain whether BoNT-A can improve activities of daily living function of paretic arm. The recovery of functions of the affected arm is also the aim of robotic upper limb (UL) therapy. The motorized exoskeleton assists the patient in a large 3D work environment by promoting movement for the UL (shoulder, elbow, wrist, hand). The combination of the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Food and Drug Administration (FDA) has approved BoT-A for the treatment of strabismus, eyelid spasm, neck dystonia, and cosmetic disorders. A large number of clinical randomized controlled trials and retrospective analyses have demonstrated that BoT-A injection reduces muscle tone, 39 expands joint mobility of affected joints, 40,41 and indirectly improves motor function of patients, 42 which makes BoT-A suitable in the prevention of muscle spasticity. 43 Toxin is a neurotoxin produced by Clostridium botulinum in anaerobic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Food and Drug Administration (FDA) has approved BoT-A for the treatment of strabismus, eyelid spasm, neck dystonia, and cosmetic disorders. A large number of clinical randomized controlled trials and retrospective analyses have demonstrated that BoT-A injection reduces muscle tone, 39 expands joint mobility of affected joints, 40,41 and indirectly improves motor function of patients, 42 which makes BoT-A suitable in the prevention of muscle spasticity. 43 Toxin is a neurotoxin produced by Clostridium botulinum in anaerobic environment.…”
Section: Discussionmentioning
confidence: 99%
“…A support > 100% could also compensate for adjunctive forces directed downwards. The device also includes an interface used for the exergame, designed to obtain task-oriented gestures in a specifically developed video game environment with exergames specifically developed for rehabilitative purposes [20,21]. The computer-robot interface is designed to provide some exergames requiring specific upper limb movements consisting of single-joint movements around a single axis or combined movements of single joint around two or three axes, exercises for the opening and closing hand (grasping exercises) and multi-joint exercises along one, two or three spatial axes (coordination exercises).…”
Section: Robotic Therapymentioning
confidence: 99%
“…The computer-robot interface is designed to provide some exergames requiring specific upper limb movements consisting of single-joint movements around a single axis or combined movements of single joint around two or three axes, exercises for the opening and closing hand (grasping exercises) and multi-joint exercises along one, two or three spatial axes (coordination exercises). The training characteristics (difficulty level, duration, visual detail) were set conforming to the residual ability of the patient [21].…”
Section: Robotic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…14 El fonksiyonları üzerine yapılan az sayıdaki çalışmada üst ekstremite robotik rehabilitasyonunun olumlu etkileri bildirilmiştir. [15][16][17] Ülkemizde bu alanda yapılmış klinik çalışmaya rastlanmamıştır. Bu çalışmada kronik inmeli hastalarda üst ekstremite robotik rehabilitasyonun el fonksiyonları ve GYA'ya katkısının incelenmesi amaçlanmıştır.…”
Section: Introductionunclassified